COMPLICATIONS RELATED COMORBIDITIES OF ARTERIOVENOUS FISTULA (AVF) CREATION AS HEMODIALYSIS ACCESS FOR END STAGE RENAL DISEASE (ESRD) IN BEN MBOI DISTRICT HOSPITAL, RUTENG FLORES INDONESIA - Gerardo Laksono; Daniel DH Silitonga; Oktavianus Y Ampur; Maria S Ganggur; Paul L Tahalele (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Introduction: Since Brescia and Cimino(1966) posted AV Fistula technique, there has been increase of long term survival of patients with End Stage Renal Disease (ESRD). AV fistula has its own set of indications, benefits, and complications. Purpose: To show AV Fistula creation outcomes, complications and its related comorbidities in Ben Mboi District Hospital, Ruteng Flores IndonesiaMethod: An analytical study design using a cross sectional approach was employed in this study. Using medical record data from 2019 to 2022, all men and women who received hemodialysis through AV Fistula were included. Bivariate analysis was carried out from baseline data such as age, sex, comorbidities, location of an av fistula (AVF), previous dialysis insertion with complications that arise using Chi-square. Results: Age, sex, hypertension and AV Fistula creation location has no significant correlation with complications such as failed to mature, thrombosis, infection, venous hypertension. Diabetes mellitus has a significant correlation with occurrence of failed to mature (p=0.012), thrombosis (p=0.014), venous hypertension (p=0.08). Obesity has a significant correlation with occurrence of failed to mature (p=0.000), thrombosis (p=0.000). Previous insertion of CDL in right subclavian vein has a significant correlation with occurrence of venous hypertension (p=0.000).Conclusion: Diabetes mellitus has a significant correlation with occurrence of complications such as failed to mature, thrombosis and venous hypertension. Obesity has a significant correlation with occurrence of failed to mature and thrombosis. History of CDL insertion in right subclavian vein has a significant correlation with venous hypertension.